Multiscale systems biology of trauma‐induced coagulopathy. (27th February 2018) - Tsiklidis, Evan; Sims, Carrie; Sinno, Talid; Diamond, Scott L.
Abstract : Trauma with hypovolemic shock is an extreme pathological state that challenges the body to maintain blood pressure and oxygenation in the face of hemorrhagic blood loss. In conjunction with surgical actions and transfusion therapy, survival requires the patient's blood to maintain hemostasis to stop bleeding. The physics of the problem are multiscale: (a) the systemic circulation sets the global blood pressure in response to blood loss and resuscitation therapy, (b) local tissue perfusion is altered by localized vasoregulatory mechanisms and bleeding, and (c) altered blood and vessel biology resulting from the trauma as well as local hemodynamics control the assembly of clotting components at the site of injury. Building upon ongoing modeling efforts to simulate arterial or venous thrombosis in a diseased vasculature, computer simulation of trauma‐induced coagulopathy is an emerging approach to understand patient risk and predict response. Despite uncertainties in quantifying the patient's dynamic injury burden, multiscale systems biology may help link blood biochemistry at the molecular level to multiorgan responses in the bleeding patient. As an important goal of systems modeling, establishing early metrics of a patient's high‐dimensional trajectory may help guide transfusion therapy or warn of subsequent later stage bleeding or thrombotic risks. This article is categorized under: Analytical and Computational Methods > Computational Methods Biological Mechanisms > Regulatory Biology Models of Systems Properties and Processes > Mechanistic Models Abstract : The global hemodynamics model is typically represented as a closed‐loop hydraulic circuit that includes lumped, zero‐dimensional, descriptions of the various components of the body. Bleeding can be included in these models by connecting the circuit to atmospheric pressure through a "resistance‐to‐hemorrhage" resistor, as is done in the Reisner–Heldt model (Reisner & Heldt, 2013). At this scale, cardiovascular output is primarily modulated by the baroreflex and transcapillary fluid shifts. At the tissue level scale (cm), vasculature branching networks are constructed to match physiological conditions before a wound occurs. Once severed, boundary conditions to model blood flow may include inlet pressure/flow conditions and an outlet pressure specification (typically atmospheric pressure). At this scale, modeling efforts should include variable resistance to flow (changing vessel diameter) to divert flow away from the site of injury. At the vessel scale (mm), parabolic flow is assumed in the healthy vessel. In the event of trauma, pressure and flow specifications are both possible, which are set by the global hemodynamic model, with the extrinsic coagulation pathway (tissue factor) being the predominant trigger for maintaining hemostasis. Transfusion, vasopressors, and clotting modulators are standard treatment options.